基于拓扑优化方法的分动器箱体轻量化设计 - 许洪斌; 鄢敏丽; 王伟; 黄德见; 黄家勇; 杨长辉 (Jixie chuandong)
Aiming at the performance characteristic of a special transfer case,a finite element model is built by using finite element method.Based on the static strength and modal analysis of the gearbox, the structure topology optimization is carried by using of the variable density method and taking minimum weighted strain energy as optimal object,displacement,volume fraction and stress as constraints. On this basis,the optimal design is carried out according to the topology density cloud,the weight of optimized gearbox is reduced by 8%.Analysis results show that,the overall performance of the optimized transfer case is improved,the lightweight design is realized.